YouTube: a learning tool in Education 4.0 - Tham, Jia Hao; Kamarudin, Nurzatulshima (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
How can YouTube improve teaching and learning in Education 4.0? The using of YouTube videos in the classroom is not new, but are we using them in the right way? To answer these questions, a review of the research is done and discussed in this paper. Education 4.0 is a response to the Industrial Revolution 4.0 by applying the advancement of technology in the education system. The generation now born in the digital phenomenon and that the use of internet platforms is more relevant to them. The earlier research had shown confidently of using YouTube videos helps in improving students learning. Hence, this article will also discuss the implementation of YouTube videos in the classroom and the techniques of teaching with YouTube.